Influence of Fatty Acid Based Collector on The Flotation of Heavy Minerals from Alkali Feldspar Ores - Kilinc Aksay, Ece; Akar, Ali; Kaya, Erol; Cocen, Ilknur (Asian Journal of Chemistry, 2010)
Turkey possesses large reserves of mainly albite feldspar ores in the western part. The principal discolouring impurities in these deposits are titanium and iron oxide, which reduce the quality and hence the revenue of the ore. Conventionally, the coloured gang minerals can be separated from albite through the use of reverse multi-stage flotation. The results of mineralogical investigation indicate that the albite ore samples of Mugla-Milas district contain mainly the high level of titanium and iron oxide minerals and small amount of mica minerals. This study showed that these main coloured impurities in the albite ore can be floated together in an alkali medium by single-stage flotation, using fatty acid based collector. It is found that Aero 704 collector achieves much superior results at 1000 g/t dosage and pH 9 compared to other anionic collectors. The results of bench scale flotation tests to evaluate the performance of this collector have been reported along with the elaboration of the mechanism of the collector action.